Effect of serum lactate dehydrogenase-to-albumin ratio (LAR) on the short-term outcomes and long-term prognosis of colorectal cancer after radical surgery - Xin-Peng Shu; Ying-Chun Xiang; Fei Liu; Yong Cheng; Wei Zhang; Dong Peng (BMC Cancer, 2023)
Abstract Background Whether serum lactate dehydrogenase-to-albumin ratio (LAR) influenced the outcomes of colorectal cancer (CRC) patients after radical surgery remained unclear. Therefore, this study sought to examine how LAR influences the short-term and long-term outcomes of CRC patients who have undergone radical surgery. Methods This study retrospectively included CRC patients who underwent radical resection between January 2011 and January 2020. We compared short-term outcomes, as well as overall survival (OS) and disease-free survival (DFS), among various groups. Both univariate and multivariate logistic regression analyses were utilized to pinpoint independent risk factors associated with overall complications and major complications. Moreover, Cox regression analysis were conducted for OS and DFS. Odds ratio (OR) and Hazard ratio (HR) were adjusted. Results This study encompassed a cohort of 3868 patients. 3440 patients were in the low LAR group and 428 patients constituted the high LAR group. In the high LAR group, patients experienced significantly longer operative times (p < 0.01), larger intraoperative blood loss (p < 0.01), and extended postoperative hospital stays (p < 0.01). Additionally, the incidence of both overall complications (p < 0.01) and major complications (p < 0.01) was higher in the high LAR group compared to the low LAR group. Furthermore, LAR was emerged as an independent prognostic factor for overall complications [OR/95% CI: (1.555/1.237 to 1.954), p < 0.01] and major complications [OR/95% CI: (2.178/1.279 to 3.707), p < 0.01]. As for long-term survival, the high LAR group had worse OS in stage II (p < 0.01) and stage III (p < 0.01). In both stage II (p < 0.01) and stage III (p < 0.01), the high LAR group exhibited poorer DFS. Additionally, according to Cox regression analysis, LAR was identified as an independent predictor for both OS [HR/95% CI: (1.930/1.554 to 2.398), p < 0.01] and DFS [HR/95% CI: (1.750/1.427 to 2.146), p < 0.01]. Conclusion LAR emerged as an independent predictor not only for overall complications and major complications but also for both OS and DFS, highlighting its significance and deserving the attention of surgeons.